Electroacupuncture at ST-36 ameliorates DSS-induced acute colitis via regulating macrophage polarization induced by suppressing NLRP3/IL-1β and promoting Nrf2/HO-1. (February 2019) - Song, Shuangning; An, Jing; Li, Yingli; Liu, Shi
Highlights: Electroacupuncture ameliorates DSS-induced acute colitis. Electroacupuncture maintains a balance of pro-inflammatory and anti-inflammatory cytokines in DSS-induced colitis. Electroacupuncture suppressed M1 macrophage polarization and promoted M2 macrophage polarization in colon. Electroacupuncture inhibited NLRP3/IL-1β activation and promoted Nrf2/HO-1 activation in colonic macrophages. Abstract: Background: Electroacupuncture (EA) at ST-36 can attenuate acute experimental colitis, but the mechanisms are unclear. We investigated the role of macrophages in the anti-inflammatory effects of EA and its molecular mechanisms. Methods: Male C57BL/6 mice were randomized into five groups: normal control, dextran sulfate sodium (DSS)-induced acute colitis (DSS), DSS with sham EA (SEA), DSS with high-frequency EA (HEA) and DSS with low-frequency EA (LEA). Body weight, colon length, DAI score and histological score were evaluated during colitis progression. Serum and colonic levels of pro- and anti-inflammatory cytokines were detected with ELISA, cytometric beads array, RT-PCR and western blotting analysis. Colonic macrophage subsets were determined using flow cytometry. Magnetic-activated cell sorting was applied to isolate colonic macrophages, and molecular mechanisms were explored with western blotting, RT-PCR and immunofluorescence. Results: (1) Compared with the DSS group, HEA and LEA attenuated body weight loss and decreased DAI and histological scores. (2) Serum levels and colonic protein and mRNA levels of IL-1β, TNFα, IL-6, IL-12 and IL17 were markedly decreased with HEA and LEA. IL-10 level was increased with HEA. (3) M1 macrophage percentage increased, while M2 macrophage percentage decreased in the DSS group; HEA and LEA reversed these proportions. (4) NLRP3/IL-1β protein and mRNA levels in isolated macrophages decreased with HEA and LEA compared with the DSS treatment group; (5) HEA increased Nrf2/HO-1 levels compared with levels in DSS mice. Conclusion: The anti-inflammatory effects of EA on DSS-induced acute colitis may rely on regulating macrophage polarization, NLRP3/IL-1β suppression and Nrf2/HO-1 promotion.